2002
DOI: 10.1007/s004360100501
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Trypanosoma rangeli: high production of infective trypomastigote forms in vitro

Abstract: In the present study, we report a simple method to induce high Trypanosoma rangeli dierentiation in vitro, producing a large number of infective trypomastigote forms. Parasites from SC-58 (Brazil) and Choachi (Colombia) strains were cultivated at 27°C in TC-100, Grace and DMEM media, each supplemented with 5% fetal bovine serum and prepared at three distinct pHs (6.0, 7.0, 8.0). Dierentiation was microscopically evaluated at 0, 3 and 6 days after cultivation in each medium by determining the percentage of tryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Other confounding factors in experimental design in later studies include insects that were periodically anesthetized for colony maintenance and problems related to infection route. Two studies reported augmented negative effects in inoculated insects (Watkins, unpublished doctoral dissertation, Koerich et al ) that were not observed in orally infected insects in the same experiment, suggesting problems stemming from the parasite injection procedure. Additionally, many studies that employed the oral infection technique did not take into account the quantity of blood consumed by each insect in the infective meal (Grewal , Tobie , Gómez , Añez , Añez et al ).…”
Section: Experimental Design and Presentation Of Resultsmentioning
confidence: 96%
“…Other confounding factors in experimental design in later studies include insects that were periodically anesthetized for colony maintenance and problems related to infection route. Two studies reported augmented negative effects in inoculated insects (Watkins, unpublished doctoral dissertation, Koerich et al ) that were not observed in orally infected insects in the same experiment, suggesting problems stemming from the parasite injection procedure. Additionally, many studies that employed the oral infection technique did not take into account the quantity of blood consumed by each insect in the infective meal (Grewal , Tobie , Gómez , Añez , Añez et al ).…”
Section: Experimental Design and Presentation Of Resultsmentioning
confidence: 96%
“…Light microscopy was performed on Giemsa-stained smears using M1011, M1014, and M1015 parasites from culture with NNN and Schneider medium supplemented with 10% fetal bovine serum by three, 10, and 17 days. Additionally, epimastigote forms of the M1011 isolate were transferred at 1 × 10 6 parasites/mL into Roswell Park Memorial Institute (RPMI) medium with 5% fetal calf serum at pH 8.0 for differentiation and acquisition of trypomastigote forms, following a protocol described by Koerich et al [ 48 ]. The percentage of trypomastigote forms was determined by counting 100 randomly selected forms on the slides.…”
Section: Methodsmentioning
confidence: 99%
“…The trypomastigotes forms were obtained by cultivating epimastigotes in DMEM medium, pH 8 . 0 at 28 xC, according to Koerich et al (2002).…”
Section: Parasitesmentioning
confidence: 99%